Alcohol use as a predictor of the course of major depressive disorder: a prospective population-based study. (27th February 2023) - Schouten, Maria J. E.; ten Have, Margreet; Tuithof, Marlous; de Graaf, Ron; Dekker, Jack J. M.; Goudriaan, Anna E.; Blankers, Matthijs
Abstract: Aims: There are indications that problematic alcohol use may negatively impact the course of major depressive disorder (MDD). However, most studies on alcohol use and adverse MDD outcomes are conducted amongst MDD populations with (severe) alcohol use disorder in psychiatric treatment settings. Therefore, it remains unclear whether these results can be generalised to the general population. In light of this, we examined the longitudinal relationship between alcohol use and MDD persistence after a 3-year follow-up amongst people with MDD from the general population. Methods: Data were derived from the Netherlands Mental Health Survey and Incidence Study-2 (NEMESIS-2), a psychiatric epidemiological prospective study comprising four waves amongst the adult Dutch general population ( n = 6.646). The study sample ( n = 642) consisted of those with 12-month MDD who participated at the follow-up wave. The outcome was 12-month MDD persistence after the 3-year follow-up, which was assessed via the Composite International Diagnostic Interview version 3.0. Weekly alcohol consumption was operationalised as non-drinking (0 drinks), low-risk drinking (⩽7 drinks; reference), at-risk drinking (women 8–13 drinks, men 8–20 drinks) and high-risk drinking (women ⩾14, men ⩾21 drinks). We performed univariate and multiple logistic regression analyses, which were adjusted for various socio-demographic and health-related factors. Results: The majority (67.4%) of the MDD sample were female, while the mean age was 47.1 years. Amongst these, 23.8% were non-drinkers, 52.0% were low-risk drinkers and 14.3% and 9.4% were at-risk and high-risk drinkers, respectively. Around one-quarter of the sample (23.6%) met the criteria for a persistent MDD after 3-year follow-up. No statistically significant association was found between alcohol use and MDD persistence, either for the crude model or the adjusted models. In comparison to low-risk drinking, the full adjusted model showed no statistically significant associations between MDD persistence and non-drinking (odds ratio (OR) = 1.15, p = 0.620), at-risk drinking (OR = 1.25, p = 0.423), or high-risk drinking (OR = 0.74, p = 0.501). Conclusions: Contrary to our expectations, our findings showed that alcohol use was not a predictor of MDD persistence after 3-year follow-up amongst people with MDD from the general population.